(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
as a result of chronic toxic effects of pesticides on the organism of the mother rat, it negatively affects the postnatal development and formation processes of vascular tissue structures of the uterus and ovaries in the offspring. The degree and severity of morphological and morphometric changes in the tissue structures of the uterus directly depends on the state of the microcirculation